SYNERGISTIC EFFECT OF 3D CURRENT COLLECTOR STRUCTURE AND NI INACTIVE MATRIX ON THE ELECTROCHEMICAL PERFORMANCES OF SN-BASED ANODES FOR LITHIUM-ION BATTERIES - Nurpeissova, Arailym; Adi, Akylbek; Aishova, Assylzat; Mukanova, Aliya; Kim, Sung-Soo; Bakenov, Zhumabay (Materials Today Energy, 2020)
A three-dimensional (3D) architecture design of the battery electrodes is believed to enhance the energy and power densities of conventional lithium-ion batteries. In this paper, we report a unique 3D architecture anode fabricated by electrodeposition of ultrathin Ni3Sn4 intermetallic alloy onto a commercially available nickel foam current collector from an aqueous electrolyte. Along with 3D nickel foam, planar (2D) copper current collector was also electrodeposited at the same deposition conditions to compare the effect of architecture. The X-ray diffraction results obtained from three-dimensional and planar anode electrodes indicated that the main phase of electrodeposited alloys for both substrates was Ni3Sn4. The designed three-dimensional electrode demonstrated a high discharge capacity of 843,75 mAh g−1 during initial cycles and an improved cycle performance over 100 cycles in contrast with the same alloy electrodeposited onto planar substrate. The high surface area of the electrode and short Li+-ions diffusion paths along with suppression of volume expansion provided by the proposed 3D structure and Ni inactive matrix play a key role in improving the performance of the electrode.
Keywords: Type of access: Open Access; Three-dimensional anode; Electrodeposition; Ni3Sn4 intermetallic alloy; Lithium-ion battery